MENGUKUHKAN METODE ‘URF KELOMPOK DALAM MELANGGENGKAN KEBERAGAMAAN UNTUK PENENTUAN BULAN QAMARIYAH TAREQAT SYATTHARIYYAH DI SUMATERA BARAT - Adlan Sanur Tarihoran (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2016)
Tareqat Syatthariyah has long grown and developed in Minangkabau, along with the entry of Islam into Minangkabau. One of developed local ‘urf and still survive and sustainable even become an annual event and habits of the fellow Syatthariyah worshipers is moon sighting (